2020
DOI: 10.3389/fpls.2020.576177
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Unmasked Nutritional Imbalances on the Medicinal Plant Bryophyllum sp. Cultured in vitro

Abstract: Plant nutrition is a crucial factor that is usually underestimated when designing plant in vitro culture protocols of unexploited plants. As a complex multifactorial process, the study of nutritional imbalances requires the use of time-consuming experimental designs and appropriate statistical and multiple regression analysis for the determination of critical parameters, whose results may be difficult to interpret when the number of variables is large. The use of machine learning (ML) supposes a cutting-edge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 86 publications
3
19
0
Order By: Relevance
“…Historically, micropropagation systems were refined using traditional statistical models to sequentially manipulate and optimize single factors. This approach often requires hundreds or even thousands of treatments to be tested, and even then sequential optimization does not account for interactions and can miss the best combinations ( García-Pérez et al, 2020 ; Hameg et al, 2020 ). Due to the cost and time requirements, most species are cultured in conditions optimized for other species with minor modifications and are not fully optimized for any given application.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, micropropagation systems were refined using traditional statistical models to sequentially manipulate and optimize single factors. This approach often requires hundreds or even thousands of treatments to be tested, and even then sequential optimization does not account for interactions and can miss the best combinations ( García-Pérez et al, 2020 ; Hameg et al, 2020 ). Due to the cost and time requirements, most species are cultured in conditions optimized for other species with minor modifications and are not fully optimized for any given application.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the micropropagation of Bryophyllum is not exempt from difficulties due to its particular metabolism and poor nutritional requirements [151]. In this sense, it was recently reported that ammonium, sulfur, molybdenum, copper, and sodium play a crucial role on growth and plantlet formation on in vitro-cultured Bryophyllum in a species-dependent manner [153]. Therefore, multiple nutritional modifications may be required to achieve genotype-specific optimization, since mineral imbalances and interactions could directly influence the success of PTC protocols, by affecting micropropagation performance [154], and causing undesirable physiological disorders [148].…”
Section: Micropropagationmentioning
confidence: 99%
“…Concerning Bryophyllum sp., the application of NFL was already applied to the identification of critical factors involved in plant in vitro nutrition [153] and organogenesis [137], as well as the production of phenolic compounds [62].…”
Section: Machine Learning For Optimizing the Biotechnological Valorizmentioning
confidence: 99%
See 2 more Smart Citations